Integrative Da'wah Strategy For Bengkulu Syarafal Anam Group In A Cultural Perspective - Cahyadi, Ashadi; Naser, Muhammad Nikman; Setiawati, Rini (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
The axiology of da'wah can actually play an important role in the development of the character of the people through various models and varied strategies. Human nature as a social being egocentrically stimulates individuals to understand and adopt the value system in their culture, environment or group. The purpose of this study is to describe the integrated da'wah strategy in the syarafal anam group. It is known that the process of da'wah can occur anywhere and anytime and people will even more quickly accept a teaching in a cultural frame. The method in this research uses a qualitative approach to phenomenological research. This paradigm holds the view that truth is not singular, but dialectical, which will depend on the context and culture of society. The results of the study show that syarafal anam can be a traditional art-based da'wah strategy, this is indicated by the activities of individuals or groups that experience a positive change in cognition, affection and behavior that is relevant to religious teachings and social values.